PENGGUNAAN PUPUK ORGANIK CAIR DARI LIMBAH SAYURAN PADA BUDIDAYA TANAMAN CAISIM (Brassica chinensis var. parachinensis) DENGAN SISTEM HIDROPONIK - Bayu Dwianjarhadi; Fadly Hairannoor Yusran; Salamiah Salamiah; Akhmad Rizali (Universitas Lambung Mangkurat, 2022)
The number of vegetables that fail to harvest or are not sold in the market causes vegetable waste that can pollute the environment, so it is necessary to reprocess it into liquid organic fertilizer. The study aimed to look at the effect of liquid organic fertilizer delivery on caisim crop production and determine the best dose of liquid organic fertilizer from vegetable waste for caisim crops. The dose of liquid fertilizer used t0 = 0 mL L-1 , t1 = 10 mL L-1, t2 = 20 mL L-1, t3 = 30 mL L-1, t4 = 40 mL L-1 with the observed parameters of plant height, leaf width, wet weight and dry weight of the plant with caisim plants as research parameters. From the results of research that has been done the use of four doses of liquid organic fertilizers from vegetable waste is able to increase the growth of caisim plants in the hydroponic method of the wick system. The best dose in caisim plant growth is in the use of a dose of t2 = 20 mL L-1 with a plant height in the fourth week of 23.68 cm, a leaf width of 8.11 cm, a wet weight of a plant of 14.44 grams, and a dry weight of 1.91 grams. The study also analyzed the production costs and business income of liquid organic fertilizer vegetable waste. The result of the production cost of liquid organic fertilizer vegetable waste amounted to Rp. 85,000 rupiah. Receipt of business income for liquid organic fertilizer vegetable waste amounted to Rp. 180,000 rupiah. From the results of production costs and business income of liquid organic fertilizer vegetable waste obtained a total income of Rp. 95,000 rupiah with the efficiency of the vegetable waste liquid organic fertilizer business Rp. 2.12 rupiah.